Frequency of human papilomavirus and associated factors in gypsy and quilombola women - José de Ribamar Ross; Natália Pereira Marinelli; Flavia Castello Branco Vidal; Elamary da Costa Fraga; Maria do Desterro Soares Brandão Nascimento; Marco Aurélio Palazzi Safádi (BMC, 2023)
Abstract Background The prevalence of Human Papillomavirus (HPV) infection in the general population is widely known, however, there are still few studies related to this infection in minority groups, Thus, the objective is to analyze the frequency of human papillomavirus and associated factors in quilombola and gypsy women. Methods Cross-sectional research with 145 quilombola and gypsy women from Caxias, Maranhão. Two Pap smear collections were performed and a questionnaire with 46 questions was applied between January, 2020 and March, 2021. Descriptive analysis and Odds Ratio with 95% confidence interval were performed. The research was approved by the ethics committee. Results There were 09 cases of atypia. The frequency of human papillomavirus was 41.37%, with a higher risk in quilombolas 55 (91.70%). Multiple infections were prevalent (53%) with high-risk genotypes 21 (35%). Types 16 and 18 together accounted for 42.85% of cases. Conclusions The frequency of human papillomavirus infection was higher than those recorded in the Northeast and Brazil, and therefore type 16 predominated. Due to limitations, the virus lineages and sublineages were not evaluated. Quilombola women had a higher rate of infection than gypsies.